2007
DOI: 10.2319/0003-3219(2007)077[0463:ssavft]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Sagittal and Vertical Facial Types and Electromyographic Activity of the Masticatory Muscle

Abstract: The results suggest that the more Class III and the more hyperdivergent type, the higher resting TMA and the lesser increase of clenching MMA than expressed by other groups. Significant differences existed in TMA and MMA according to sagittal and vertical facial skeletal types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
46
0
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 28 publications
11
46
0
12
Order By: Relevance
“…Some articles reported that the longer the face of an individual, the greater the EMG activity of the temporal muscle. 3,8 Still others report that this muscle activity does not present any correlation with vertical face morphology. 4 On the other hand, there are studies that do not show differences in the EMG activity of the masseter muscle when com- 8 According to Farella et al 7 and Cha et al, 8 the habitual activity of the masseter muscle does not seem to be influenced by the vertical craniofacial morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some articles reported that the longer the face of an individual, the greater the EMG activity of the temporal muscle. 3,8 Still others report that this muscle activity does not present any correlation with vertical face morphology. 4 On the other hand, there are studies that do not show differences in the EMG activity of the masseter muscle when com- 8 According to Farella et al 7 and Cha et al, 8 the habitual activity of the masseter muscle does not seem to be influenced by the vertical craniofacial morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Their function and anatomy have been evaluated by electromyographic (EMG) exams, [1][2][3][4][5][6][7][8][9] bite force, 10 computed tomography of muscle thickness, 11 ultrasonography 5,[12][13][14][15] and magnetic resonance, 16 in addition to immunohistochemistry evaluations of muscular fibers. 17 EMG evaluations of masticatory muscles have produced divergent results when individuals with different vertical facial growth are compared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, EMG was chosen for the analyses of correlation between the ME test with beads and the reliability of the methods because it is a widely used and accepted method for the investigation of masticatory muscle function (8)(9), permitting the characterization of functional problems, guiding prevention and rehabilitation actions in the speech therapy (22) and dentistry (10,11,13) area, as well as favoring the analysis of the results of treatment (12,14).…”
Section: Resultsmentioning
confidence: 99%
“…EMG has been extensively used in research, is considered to be a valid method for the assessment of masticatory muscle function (8)(9)(10)(11)(12)(13)(14) and has been correlated with masticatory efficiency (15-17).…”
Section: Introductionmentioning
confidence: 99%